KARAKTERISARI GUGUS FUNGSI DAN BOBOT MOLEKUL KARET MODIFIKASI LIQUID NATURAL RUBBER (LNR) MELALUI DEGRADASI OKSIDATIF FENIL HIDRAZIN/O2 DENGAN PENAMBAHAN EMULSIFIER TRITON-X 100 - Eddiyanto Eddiyanto (PROSIDING SEMINAR KIMIA, 2020)
The research has been done the preparation of chemical modification natural rubber (Liquid Natural Rubber) by using latex high ammonia natural rubber (60 % drc), Triton X-100, phenylhydrazine, and oxygen. High ammonia natural rubber was diluted to 30 % by using 0.3 phr Triton X-100 as emulsifier at room temperature for 12 hours and continued oxidative degradation at 60oC using 1,75 x 10-1 mol phenylhydrazine and oxygen with flowrate 2 l/min for 24 hours until it became arising the decomposition with random cleavages and the macromolecular weight. The product of Liquid Natural Rubber has been result showing the significant infrared absorption with wavenumber 1665 cm-1and the molecular weight by using Ostwald viscosimetry 8.71 x 101 g/mol. Keywords : Chemical modification, Liquid Natural Rubber,Triton X-100, Ostwald viscosimetry.